(untitled) (Research, Society and Development, 2020)
Using the potential of growth-promoting bacteria in the growth and perennially of pastures can be a new strategy for managing pastures, minimizing the chances of degradation, and improving productivity and forage quality. Thus, the objective was to evaluate the production of Urochloa ruziziensis inoculated with bacteria that promote plant growth and nitrogen fertilization. Leaf mass production, total forage mass production, root production and chlorophyll content of U. ruziziensis cultivated in soil originating from sandstone and in a sterile substrate were evaluated, inoculated with five BPCV (Azospirillum brasilense Ab-V5 and Ab-V6, Pseudomonas fluorescens CCTB 03 and ET76 and Pantoea ananatis AMG521), in addition to uninoculated control and in combination with N-fertilizer doses (zero, 50 and 100 kg ha-1 of N), in a 6x3 factorial scheme under greenhouse conditions. In general, bacteria when inoculated without the addition of N-fertilizers (zero dose) were more efficient in the production of leaf forage mass in the different cuts, total forage mass, root mass production and crude protein concentration. It is noteworthy that inoculation with P. fluorescens and P. ananatis AMG521 proved to be more effective than the other strains used in the studied variables. The inclusion of bacteria that promote plant growth as pasture management is an excellent tool for growing ruziziensis grass with an increase in the production of forage mass and root mass, in addition to reducing the consumption of nitrogen fertilizers.